VARIASI IKAN HIU DAN PARI APPENDIX II CITES HASIL TANGKAPAN NELAYAN DI PELABUHAN PERIKANAN NUSANTARA BRONDONG LAMONGAN - Marandi Eko Wibowo; Marita Ika Joesidawati (Techno-Fish, 2023)
The activity of catching sharks and rays around the world have exceeded catch limits, causing some species to be in danger or extinct. Indonesia is one of the countries that still allows fishing for sharks and rays. Lots of fishermen at Pelabuhan Perikanan Nusantara Brondong have been fishing sharks and rays for several generation.so that it can be causing several species of sharks and rays in Indonesia are threatened. Knowing attachment of APPENDIX II CITES, sharks and rays have become a major concern in fisheries management and marine conservation around the world. Many of these groups are endangered due to massive exploitation over the past few decades. Some species of sharks and rays have been enrolled on attachment of APPENDIX II CITES, which controls international trade in endangered species.